An IT service management literature review: Challenges, benefits, opportunities and implementation practices - Serrano, J. (2021)
Information technology (IT) service management is considered a collection of frameworks that support organizations managing services. The implementation of these kinds of frameworks is constantly increasing in the IT service provider domain. The main objective is to define and manage IT services through its life cycle. However, from observing the literature, scarcely any research exists describing the main concepts of ITSM. Many organizations still struggle in several contexts in this domain, mainly during implementation. This research aims to develop a reference study detailing the main concepts related with ITSM. Thus, a systematic literature review is performed. In total, 47 articles were selected from top journals and conferences. The benefits, challenges, opportunities, and practices for ITSM implementation were extracted, critically analysed, and then discussed.